Enhancing security and observability of distribution systems with optimal placement of μPMUs and firewalls - Sohrabi Tabar, Vahid; Tohidi, Sajjad; Ghassemzadeh, Saeid; Siano, Pierluigi (International journal of electrical power & energy systems, 2022)
•Proposing a two-level multi-objective method to investigate the observability and security.•Utilizing a virtual connection method to optimize the places of μPMUs with ZIBs.•Analyzing the security of system by determining the optimal placement of firewalls.•Presenting a reserve method based on critical data points to overcome the uncertainty of μPMUs.•Considering firewall limitation, SCADA measurements and power system expansion. Access to the power system information in the shortest time with the highest accuracy has become critical because of changing the system dimension, cyber-physical issues and increasing data points. This paper evaluates the security and observability of distribution systems under two-level modelling consist of power system observability and security of data points. In the higher level, optimal places of μPMUs are obtained by considering a virtual connection method and optimizing a multi-objective function. In the lower level, a security index is introduced and then the system is analyzed based on security and cost functions. In this regard, firewalls are used and appropriate locations are determined to secure each data point. It is worth mentioning that various subjects including limitation of components, impact of zero injection buses and pre-installed measurements, failure of μPMU and the process of power system expansion have been investigated. To evaluate the method, simulations are implemented on the 69-bus and 123-bus standard distribution systems. The comparative results for the 69-bus system validate that the virtual connection method reduces the number of required μPMUs and decreases the investment cost by about 8.75%. Furthermore, the system can be robust against cyber-physical issues and a specific percentage of observability will be guaranteed by a limited number of firewalls and μPMUs.